Efficiency Analysis Of Zakat Institutions In Indonesia: Data Development Analysis (DEA) And Free Disposal Hull (FDH) Approaches - Ryandono, Muhamad Nafik Hadi; Qulub, A Syifaul; Cahyono, Eko Fajar; Widiastuti, Tika; Nur Aisyah; Robani, Anidah (Allied Business Academies, 2021)
This study aimed at assessing the efficiency of zakat organizations in Indonesia by the use of non-parametric efficiency measurement methods. In addition, a cluster analysis based on the affiliation type was also used to assess the efficiency of Zakat organizations. A quantitative approach with the DEA and FDH methods was applied to this research, during which the latest data from the financial reports of each Zakat Institution have been utilized. This period ranges from 2014 to 2018 for the 14 Zakat Institutions. Based on the results, Zakat Institutions have equal efficiency between DEA and FDH methods if the clusters of government, corporation, and social community are combined. Research data on measuring efficiency show that the DEA method contributes 21% of all Decision-Making Units (DMU) to the total, while the FDH method contributes 25%. The research is one of the first studies to focus on the efficiency of the Zakat Institutions and its associated clusters: government, corporation, and social community. This research can be useful for Zakat Institutions in the form of critical application evaluation considering the research input variables, such as salaries, operational costs, and cost of socialization, and research output variables, for example zakat fund, zakat distribution taking maqasid sharia aspects into consideration.